Concurrent thymic carcinoma and middle lobe syndrome - Zheng, Xi; Huang, Yue; Gou, Junhe; Zhu, Daxing; Zhou, Qinghua (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Surgery is one of the rst-line treatments for thymic carcinoma. Middle lobe syndrome which is irresponsive to conservative therapies also calls for surgical intervention. We reported the case of a 65-year-old male who was diagnosed with coexistent thymic carcinoma and non-obstructive middle lobe syndrome. Before the operation, we took measures including repeated sputum examination, physical therapy, postural sputum drainage and bronchodilator inhalation. After removal of the mediastinal neoplasm, venous antibiotics were used to prevent pneumonia. The preexistent cough with purulent expectoration still lasted, but no pulmonary infection occurred. Our report indicates that middle lobe syndrome may not increase respiratory complications after midline sternotomy if it receives proper treatments before the operation. For patients with concurrent thymic carcinoma and persistent middle lobe atelectasis, the thymic tumor might be treated with priority to increase the chance of complete resection.